2017
DOI: 10.1111/acv.12364
|View full text |Cite
|
Sign up to set email alerts
|

Post‐reintroduction distribution and habitat preferences of a spatially limited island bird species

Abstract: Investigating habitat use and preferences of a threatened species can be challenging, especially if wild populations have decreased to such low numbers that they occupy only fractions of their former natural range. Hence, assessing habitat suitability of a potential release site for a threatened species before a reintroduction attempt can be difficult because frequently no comparable baseline data are available. In these instances, post-release monitoring data can inform about habitat use and preferences of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Reintroduction is a restoration program in which animals are translocated to areas within their historic range when the population and habitat of the animal there have decreased (Conant, 1988). The role of captive breeding and reintroduction programs that aim to augment or reestablish wildlife populations has increased dramatically (Ebenhard, 1995), including the endangered banteng (Bos javanicus d' Alton, 1823), into parts of its former natural range (Armstrong & Seddon, 2008;Moorhouse, Gelling & Macdonald, 2009;Massaro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Reintroduction is a restoration program in which animals are translocated to areas within their historic range when the population and habitat of the animal there have decreased (Conant, 1988). The role of captive breeding and reintroduction programs that aim to augment or reestablish wildlife populations has increased dramatically (Ebenhard, 1995), including the endangered banteng (Bos javanicus d' Alton, 1823), into parts of its former natural range (Armstrong & Seddon, 2008;Moorhouse, Gelling & Macdonald, 2009;Massaro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A study on released otters similarly found that the movement (i.e., exploration) distance of individuals released into unoccupied areas was much lower than those released into areas containing conspecifics (Sjoasen, 1997). Density‐dependent dispersal (Massaro, Chick, Kennedy, & Whitsed, 2018) is therefore a likely driver of greater settlement distance in second‐year animals. However, these second‐year animals did settle faster than those released in the first year (Figure 3b), possibly spending less time searching for appropriate habitat near to release sites and dispersing immediately out of the large forest blocks into empty territories.…”
Section: Discussionmentioning
confidence: 99%
“…• Post-release resource use, where expectations based only on relict populations are unlikely to anticipate the full range of potential responses of the reintroduced population under novel conditions (Mihoub et al, 2014;Massaro et al, 2018).…”
Section: Noveltymentioning
confidence: 99%